Language Learning Strategies used by the Extrovert and Introvert Students at the Third Years Students of STITNU Sakinah Dharmasraya - Siska, Widia (Riwayat: Educational Journal of History and Humanities, 2025)
Personality is one aspect that influences a student's learning process. In general, there are two types of student personality, open (extrovert) and closed (introvert). Students with open personalities will have learning strategies that tend to like working together with classmates and students with closed personalities also tend to work together to avoid bad judgment from teachers and classmates because they have a quiet nature. This research aims to see what learning strategies are used by students with open and closed personalities. The respondents of this research were 60 STITNU Sakinah Dharmasraya students consisting of 30 students with open personalities and 30 students with closed personalities who were taken using stratified sampling techniques. In collecting data, researchers used 2 types of questionnaires. The first questionnaire aims to find students' personality types between extrovert and introvert and the second questionnaire aims to find students' English learning strategies. From the research results, it was found that students with extrovert personalities used social strategies and students with introvert personalities used affective strategies.